Soundscapes of change: Creativity, commodification, and cultural identity in Thai classical music recordings - Saisuk, Kanlayanee; Amatyakul, Poonpit; Pidokrajt, Narongchai (Edelweiss Applied Science and Technology, 2025)
This study explores the transformation of creative production in the Thai classical music recording industry, focusing on four key aspects: repertoire, performance styles, visual identity, and artist groups. The study uses qualitative research to analyze historical trends, sociocultural influences, and technological advancements affecting Thai classical music recordings. Data were collected through archival research, interviews with industry professionals, and examining recorded materials. The study reveals that repertoire and performance styles have evolved from complex compositions performed by traditional ensembles to more accessible solo instrumental works. The visual identity has shifted from traditional Thai aesthetics to modern graphic designs, reflecting globalized influences. Artist groups have transitioned from kinship-based ensembles to institutionally affiliated productions, with organizations like the Fine Arts Department shaping recording trends. These transformations reflect broader shifts in the commodification of music, digital technology’s impact, and the challenges of cultural heritage preservation. The findings enforce the need for strategies which can adapt and balance tradition with innovation to sustain the Thai classical music industry while preserving its cultural authenticity. This study contributes to the literature on ethnomusicology and cultural preservation, offering insights into the interplay between modernity and tradition in a rapidly changing market.